Health risk assessment of mercury in marine fish and formulation of its consumption advisory for reproductive aged women in selected areas in Selangor - Deligannu, Pravina (2016)
Mercury is a potential toxicant that can permanently damage brain, kidney and developing fetus. Fish consumption has been identified as the major exposure route. Being one of the highest marine fish consuming communities in the region, Malaysians are probably at mercury exposure risk. This study was undertaken to assess the health risk of mercury via marine fish intake and to formulate its‟ consumption advisory among reproductive-aged women, one of the most sensitive group. This was a comparative cross-sectional study, conducted in urban and coastal rural part of Selangor. Women ages between 18 to 49 years old (n=311) participated in the community survey which included screening, interview, anthropometric measurements and hair sample collection. Nineteen commonly consumed marine fish species were identified from interview responses and purchased from five selected fish markets (n=175). Multiwave 3000 (Anton Paar) was used to digest the hair and fish samples while VP90 cold vapor AAS was used for THg quantitation in the samples. Statistical analyses were performed using IBM SPSS version 21. The predictors of THg accumulation in fish muscles, the non-carcinogenic health risk for women, and dietary pattern for THg exposure and the contributors for THg accumulation in hair samples were determined which led to the formulation of marine fish consumption advisory. Analysis showed that the geometric mean THg in fish muscles was 0.31μg/g, with 9% exceeded the WHO guideline (0.5μg/g). Fish with greater weight, live in the demersal ecosystem and of higher trophic levels (≥ 4.0) significantly accumulated more THg (p<0.05). Marine fish intake rate differed significantly between coastal rural and urban women (median = 691.1 vs 516.4 g/week; p<0.003). Consistently, hazard quotient showed that coastal rural women had higher non-carcinogenic health risks than their urban counterpart. Likewise, hair THg was significantly higher among coastal rural women compared to urban (median = 0.98 vs 0.82 μg/g; p<0.030). However, there was no significant difference between the two groups in percentage exceeding the reference dose (49.0 vs 40.9%; p=0.150). Five principal components (PC) were retained as dietary patterns for Hg exposure but only three were selected based on the elbow of scree plot (54.5% variation). The patterns were Pelagic Fish Diet (PC1&PC3) and Demersal-Predatory Fish Diet (PC2). The significant contributors to hair THg were marital status, the percentage of total body fat, eating fish angled from marine water environment and Hg exposure from pelagic as well as demersal-predatory fish diet (28.3% variation). The formulated consumption advisory showed that marine fish can be consumed for a maximum of 14 servings / week (1 serving ~ 85g). Nevertheless, predatory fish should be limited to 3 - 4 servings / week. As a conclusion, there were Hg contaminations in marine fish species analyzed and possibilities for Hg exposure risk. The formulated consumption advisory identified the types of marine fish that has to be limited which allows the sensitive populations to be continually protected from dietary mercury exposure.